Hellboy. The crooked man [videorecording (DVD)] - Mignola, Mike (Ketchup Entertainment, 2024)
Hellboy and rookie BPRD agent Song find themselves stranded in 1950s Appalachia, where they discover a community of witches led by a sinister evil called The Crooked Man, with mysterious ties to Hellboy's past.